2011
DOI: 10.1167/iovs.11-7747
|View full text |Cite
|
Sign up to set email alerts
|

Normative Database for Corneal Backscatter Analysis by In Vivo Confocal Microscopy

Abstract: Sex and time of measurement significantly affect corneal backscatter measured by IVCM, whereas age affects only backscatter in the anterior stroma. All three factors should be taken into account when conducting scientific research. For ophthalmic practice, the authors suggest ignoring these factors and propose a generalized normal range and minimum detectable change for each backscatter variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 26 publications
(33 reference statements)
4
35
2
1
Order By: Relevance
“…Previously, some literatures [2,15] reported significantly increase of corneal density with age and some reported contradictory findings [4,16,17]. However, this study observed a significant increase in corneal density of about 2-3 GSU with each increment of a decade of age.…”
Section: Discussioncontrasting
confidence: 62%
“…Previously, some literatures [2,15] reported significantly increase of corneal density with age and some reported contradictory findings [4,16,17]. However, this study observed a significant increase in corneal density of about 2-3 GSU with each increment of a decade of age.…”
Section: Discussioncontrasting
confidence: 62%
“…7 While we attempted to age-match our subjects with Fuchs dystrophy and normal corneas, the mean age of the normal group was younger. Despite this limitation, increasing age is minimally associated with increased corneal backscatter, 32 and the 4% per decade decrease in stromal cells 33 would not explain the magnitude of the cell loss in this study. The stromal cell densities reported in this study appear lower than those in our previous study 12 because unlike the previous study, we were unable to correct the densities for the effect of corneal edema (surgical intervention was performed in the previous study which enabled measurement of postoperative host stromal thickness).…”
Section: Discussionmentioning
confidence: 62%
“…Other methods of evaluating corneal transparency are optical coherence tomography (OCT) [22] and in vivo confocal microscopy (IVCM) [23]. …”
Section: Discussionmentioning
confidence: 99%